Hard-magnetic cell microscaffolds from electroless coated 3D printed architectures. Issue 4 (29th May 2018) - Bernasconi, Roberto; Cuneo, Federico; Carrara, Elena; Chatzipirpiridis, George; Hoop, Marcus; Chen, Xiangzhong; Nelson, Bradley J.; Pané, Salvador; Credi, Caterina; Levi, Marinella; Magagnin, Luca
Abstract : We report the application of 3D printing and wet metallization to the fabrication of magnetically driven microscaffolds for cell delivery. Abstract : The combination of 3D printing and wet metallization is a promising methodology for the manufacturing of functional microdevices able to carry out biomedical tasks in vivo . Following this approach, prototypical cell scaffolds are successfully manufactured in the present work. Functional layers are sequentially deposited employing electroless metallization on stereolitography 3D printed moveable structures. Final devices are characterized and magnetically actuated in a precise way using a novel rolling motion approach, which allows for a superior control over speed and position. From the living cells compatibility point of view, the scaffolds show good biocompatibility with fibroblasts after the application of a gold layer.